Regional Public Services Agency Income, Retribution Revenue, and Non-Capitation Funds BPJS Health at Kemayoran District Public Health Center, Central Jakarta Administration City - Sri Setiawati; Ahmad Muhammad Thantawi; Isnaini Hijriyah Kurniasari; Yanti Budiasih; Amanda Lestari Putri Lubis; Fahmi Iskandar (Journal of Healthcare and Biomedical Science, 2023)
Regional Work Unit of Regional Public Services Agency has been granted the authority to manage the income generated by the services provided to the public in order to improve service quality. Retaliation is deducted from the costs of medical care that the uninsured patient pays. Whereas, Non-capitation funds paid by the Health Social Security Administrator (BPJS Kesehatan). This study aims to know the effect of Health Service Retribution Revenue and Non-Capitation funds of the revenue of BPJS Health toward income, how great the impact is. This study is done in Public Health Center in Kemayoran District. Quantitative method is used as the method of the study. And secondary data is used as the data of the study. Classical Assumption Test and Hypotheses Testing, such as multiple regression equations, are used as the statistic method. T test and f test with significant level 5%. The data is processed using SPSS 25 program. The results are based on Retribution Revenue data, Non-Capitation funds, and Regional Public Services Agency of Public Health Center Revenue in Kemayoran District in 2014 to 2018. All of the data showed that Retribution Revenue data, Non-Capitation funds and Regional Public Services Agency of Public Health Center Revenue results, significantly and positively toward BPJS services.